Online business platform preferences using fuzzy COPRAS-G / Husna Izzaty Mat Zahir - Mat Zahir, Husna Izzaty (2021)
The rapid growth of online shopping is driving the growth of online business. As a result, online business owners need to be prudent in developing a strategy to market and sell their products. One strategy is to choose a good platform to run an online business. There are, however, many online business platforms available on the internet. So choosing an online platform is not easy. In addition, there are also many criteria that need to be considered when selecting online business platforms. The aim of this study was to determine the most important criterion in the choice of online business platforms and to rank online business platforms. Four online business platforms, namely Facebook, Instagram, Twitter and Shopee, were ranked in this study on the basis of three criteria: content efficiency, networking and security. The data for this study were collected from three online business owners and ranked using fuzzy COPRAS-G. The effectiveness of content and networking has been identified as the two most important criteria for choosing online business platforms. Instagram has also been found to be the most preferred platform for online business, while Facebook is the least preferred. This has shown that Instagram is a platform that provides a good place for online business owners to run their online business. This study has shown that the fuzzy COPRAS-G is a simple and good method of ranking online business platforms. The result of this study could be a reference for new online business owners to choose the right platforms for their business. This study can also be a guide for existing online business owners to improve their businesses.